Attainment, attendance, and school difficulties in UK primary schoolchildren with probable ADHD. (2nd August 2020) - May, Felix; Ford, Tamsin; Janssens, Astrid; Newlove‐Delgado, Tamsin; Emma Russell, Abigail; Salim, Javid; Ukoumunne, Obioha C.; Hayes, Rachel
Abstract : Background: Among children aged 6–16, there is a clear association between attention‐deficit/hyperactivity disorder (ADHD) symptoms and academic attainment. We wanted to know whether this association was replicated in younger children. Aims: To explore the relationship between children aged 4–8 with probable ADHD and their academic attainment and school attendance. Secondly, the study aimed to explore their behaviour within school and their reported attitudes towards school. Sample: A total of 1, 152 children who were taking part in the Supporting Teachers and Children in Schools (STARS) cluster randomized controlled trial. Methods: ADHD status was established by using the Strengths and Difficulties Questionnaire predictive algorithm to identify children with probable ADHD. Using baseline data, random‐effects regression models on ADHD status were fitted to attainment, attendance, special educational needs (SEN) provision, and attitudes towards school and classroom behaviour; models that were also fitted to attainment were evaluated again at 9, 18, and 30 months after baseline. Results: Children with probable ADHD ( n = 47) were more likely than controls ( n = 1, 105) to have below‐expected attainment in literacy (odds ratio (OR) 16.7, 95% CI 6.93‐to‐40.1), numeracy (OR 11.3, 95% CI 5.34‐to‐24.1) and to be identified as having SEN (OR‐55.2, 95%‐CI 22.1‐to‐137). Their attendance was poorer with more unauthorized absences (rate ratio (RR)‐1.91, 95%‐CI‐1.57‐to‐2.31). They had more teacher‐reported behavioural problems (mean difference (MD) 5.0, 95%‐CI 4.6‐to‐5.4) and less positive attitudes towards school (MD −1.1, 95% CI −0.56 to −1.85). Poorer attainment in literacy and numeracy persisted at all follow‐ups. Conclusions: Children aged as young as 4 whose behaviour indicates probable ADHD struggle to cope at school in terms of academic attainment, attendance, classroom behaviour, and attitude towards school when compared to other children. Early identification and intervention to help these children manage in school are needed.